Potensi Membran Keramik Dari Tanah Liat Dan Fly Ash Batubara Untuk Mengolah Air Gambut Menjadi Air Bersih - Mutia Putri; Lita Darmayanti; Edward HS (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
The supply of clean water in Riau Province can only reach urban areas, thus encouraging some people in rural areas to use peat water to meet their needs. Peat water does not meet the specified clean water quality standards because it has the characteristics of a brownish red color, low acidity and high organic matter content. One of the ways to treat peat water into clean water is by using a ceramic membrane filtration process. Therefore, this article will present a brief review of the potential of ceramic membranes to treat peat water into clean water.Keywords: peat water, ceramic membrane, filtration